Microcomputer-based laboratory (MBL) in chemistry teaching - Tolvanen, Simo (LUMAT-B: International Journal on Math, Science and Technology Education, 2016)
Microcomputer-based laboratory (MBL) or computer assisted generation and manipulation of data, can be exploited widely in practical work. This article goes through aims set for practical work, and ideas in exploiting microcomputer-based laboratory equipment especially in inquiry-based work are offered.